Impact of the COVID-19 Pandemic on Functionality and Fall Risk in Institutionalized Geriatric Patients: A Longitudinal Observational Study - Javier Torralba Estelles; Jorge Velert Belenguer; Elena Martinez Mendoza; Javier Ferrer Torregrosa (Life)
Background: The global impact of the COVID-19 pandemic has significantly influenced elderly functionality, particularly in terms of balance, gait, and independence in daily activities. This study sought to evaluate how these aspects have changed over the course of the health crisis. Methods: We employed the Tinetti scale for assessing balance and gait, and the Barthel Index for measuring functional independence, conducting a comparative analysis of scores before and after the onset of the pandemic in a sample of elderly individuals. Results: Our findings indicated an increase in Tinetti scores, suggesting some improvement in balance and mobility, albeit with marked variability across participants. On the other hand, Barthel scores showed a significant decline, pointing to a reduction in functional independence. Conclusions: These results suggest that the impact of COVID-19 on elderly functionality is not uniform, highlighting the need for personalized rehabilitation strategies. Such strategies should not only focus on physical recovery but also consider the psychological and social repercussions of the pandemic to fully address the diverse needs of this vulnerable population.